A Methodological Framework for the Interdisciplinary Literary Text Analysis - Labinska, Bohdana; Osovska, Iryna; Matiychuk, Oxana; Vyspinska, Nataliia (East European Journal of Psycholinguistics, 2020)
All scientific endeavours require researchers to develop an understanding of the available methodological tools to perform the needed studies. These tools can be applied depending on the field, purpose and context of the study. This article outlines and argues for ways to construct methodological framework appropriate for an in-depth interdisciplinary analysis of a literary text. The purpose of this study is to build the interdisciplinary methodological framework for literary text analysis using approaches of two humanities sciences – pedagogy and philology (linguistics and literature). The material for the research is a contemporary fairy tale Bunny Non-Hopper and His Brave Mommy by Oksana Drachkovska, Ukrainian writer and journalist. Relevance, innovation, importance and complexity of the author’s fairy tale theme, which appears both in the field of modern pedagogy and current philological interpretations justified our choice. Among the methods applied in the paper are literary studies interpretation that outlines a place of the fairy tale in the context of similar Ukrainian and foreign literature and reveals features of the its gender constructions; linguistic analysis based on communicative-pragmatic and conceptual approaches that focus on the text-discursive level along with pedagogical approaches that enable the representation of the text’s educational potential. The suggested framework consists of two levels – general scientific and specific scientific. On the general scientific level, it deploys systematic, synergetic, and paradigmatic approaches, whereas on the specific scientific level – linguistic approaches (communicative pragmatic and conceptual), literary studies approaches (intertextual and gender), and pedagogical approaches (integrated, inclusive, humanistic, empowerment), thus employing knowledge and specifics of each science. Besides a system-building function aimed to obtain comprehensive information about the object of the study, the proposed methodological framework for the interdisciplinary literary text analysis embraces an anthropocentric paradigm centred on children with special educational needs.